Preparation and Characterization of Activated Carbon from Household Waste Foods - Iman Hussein Zainulabdeen (Tikrit Journal of Engineering Sciences, 2017)
Waste food residues are considered as suitable raw materials for the production of low cost adsorbents. In this work, activated carbons was perpetrating from household waste food (orange peels, banana peels, walnut shells, olive stones and their mixture).  Chemical carbonization at 500?C for 1.5hr was used to prepare carbons and their activation by KOH and CaCl2 solutions for 24h. Then added 0.1g of activated carbons to the solution of blue dyeprepared laboratory to demonstrate the activation of the types of activated carbons prepared toremove the blue dye. The results indicated that characteristics (yield, burn off, density, moisturecontent, ash content, pore volume, porosity percent, Iodine number, methyl blue number andremoval percent of methyl blue) for all activated carbons were compared with commercialactivated carbon. It has been found that activated carbon from orange peels and mixturesactivated with CaCl2 had the best adsorption properties reach to the (80, 77.5)% removal bluedye respectively and iodine numbers (741, 735)mg/g . This low coast activated carbons can beused for wastewater treatment.